Investigation of the moisture conductivity of pine wood by trunk height - Kantieva Ekaterina; Snegireva Svetlana; Platonov Aleksey; Kiseleva Aleksandra (BIO Web of Conferences)
The hydrothermal treatment process is one of the most energy-intensive in wood processing technology, including dewatering and moistening of wood. The hydrothermal treatment process is one of the most energy-intensive in wood processing technology, including dewatering and moistening of wood. The hydrothermal treatment process is one of the most energy-intensive in wood processing technology, including dewatering and moistening of wood. The processes of dewatering or drying of wood are carried out in natural conditions, in drying or steaming chambers. Obtaining a high-quality dried material with minimal internal stresses is possible based on information about the value of the moisture current in the wood, expressed in terms of the moisture conductivity coefficient. The moisture content coefficient depends on the density and humidity of the wood, the direction of moisture flow, temperature, etc. As the temperature rises and the humidity of the wood decreases, the intensity of the moisture current also increases. With a decrease in the moisture content of wood, the value of the diffusion moisture current in it increases. The available information on the moisture content of wood does not take into account the variability of the density of wood in the height of the tree trunk and is presented for the butt part of the trunk. The determination of the moisture conductivity coefficient was established in the radial and tangential directions for sound pine wood, taking into account the height of the trunk by the method of stationary moisture current. Experimentally, an increase in the value of the moisture conductivity coefficient of the pine wood along the trunk height in the radial and tangential directions in the middle part of the trunk by 1.6 times, and in the upper part by 2.05 times compared with the lump. In pine wood, the current intensity in the radial direction is higher than in the tangential direction in wood from the butt part of the trunk by an average of 14.0%, from the middle part of the trunk by 5.0%, and from the apex by 16.0%, regardless of the ambient temperature. The obtained patterns on the variability of the moisture conductivity coefficient of pine wood along the trunk height show the expediency of carrying out preliminary sorting of wood before hydrothermal treatment, taking into account its location in the tree trunk. This will make it possible to optimize the processes of drying and drying of wood, to justify rational modes of chamber and atmospheric drying.